PERJUANGAN KE ARAH SUPERIORITAS TOKOH AUGUST DALAM FILM WONDER - Mogea, Tasya Sheilla Debora; Sigarlaki, Stephani J.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â This research is entitled â€œStriving for Superiority of August as Seen in Wonder Filmâ€ is intended as a requirement to accomplish the bachelorâ€™s degree at Faculty of Humanities Sam Ratulangi University Manado. This research focus on the psychological condition of August, the actions striving for superiority of August. The purposes of this research are to identify, classify, analyze, and describe the striving for superiority actions of August and the factor that causes the striving for superiority of August. This research used descriptive qualitative method by Bogdan and Biklen (1982). In identifying, classifying, and analyzing the data, the writer used two theories of individual psychology by Adler to analyze the striving for superiority and to analyze the factor causes striving for superiority by Adler (in Boeree, 2005:135). The results of this research are August did two actions striving for superiority, that are compensation and superiority complex. The factor that causes the striving for superiority of August is an action for filling of a desire and potential, which encourages for attaining of a goal.Keywords: Superiority, Inferiority, Wonder, Psychology